Pengembangan Literasi Di Kelurahan Pasar Siborongborong - Rosian Uli Sibagariang; Sharlin Elviyana Harefa; Emmi Silvia Herlina (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
Developing literacy for children in Pasar Siborongborong Village aims to improve children's communication and social skills. The ability to read and write allows children to express their ideas, feelings and thoughts more clearly and effectively. Methods or techniques that are often used in developing literacy for children in Pasar Siborongborong Village include the Book-Based Approach, Reading Aloud and the method of using reading application technology. The service carried out not only succeeded in improving technical literacy skills, but also fostered a positive attitude towards learning and developed characters that support children's academic and social success. These results underline the importance of continuing literacy development programs and the involvement of various parties in supporting children's education.